An Indirect Comparison Between Nivolumab + Ipilimumab + Two Cycles of Chemotherapy vs. Pembrolizumab + Chemotherapy as First-Line Treatment for Metastatic Non-Small Cell Lung Cancer - Jiang, Panpan; Mao, Ziyang; Wang, Qinyang; Jia, Xiaohui; Geng, Luying; Xu, Hong; Jiang, Lili; Yang, Chengcheng; Jiao, Min; Guo, Hui (Frontiers in Oncology, 2021)
Background Nivolumab + ipilimumab + two cycles chemotherapy (N-I + chemo, intensive immunotherapy but chemo-light) and pembrolizumab + chemotherapy (Pem + chemo) were both recommended as first-line treatment for metastatic non-small cell lung carcinoma (NSCLC) patients. We conducted this indirect comparison to compare the efficacy of and safety between these two treatments for providing reference for decision making. Methods Relevant databases were searched for eligible trials. A well-accepted adjusted indirect treatment comparison (ITC) approach was selected to pool efficacy results and safety outcomes. Subgroup analyses were stratified according to PD-L1 expression and clinical characteristics. Results Four eligible randomized trials (CheckMate9LA, KEYNOTE-021G, KEYNOTE 189, KEYNOTE 407) involving 2017 patients were available to analyze. The ITC results suggested that N-I + chemo is comparable to Pem + chemo in OS (HR 1.03, 95% CI 0.82-1.30) and ORR (RR 0.81, 95% CI 0.62-1.06), but tended to yield inferior PFS (HR 1.28, 95% CI 1.04-1.59) than did Pem + chemo. As for safety profiles, N-I + chemo showed no significant difference relative to Pem + chemo in any grade adverse events: (RR 1.03, 95% CI 0.99-1.10), but demonstrated reduced toxicity in chemo-related adverse events, such as anemia (RR 0.63, 95% CI 0.49-0.81), neutropenia (RR0.51, 95% CI 0.33-0.79), and thrombocytopenia (RR 0.38, 95% CI 0.21-0.69). Conclusions N-I + chemo is a promising treatment option for providing comparable OS related to Pem + chemo. However, for never smoker female patients, Pem + chemo is preferable to choose for demonstrating favorable OS benefit than N-I + chemo.